2007
DOI: 10.1557/jmr.2007.0444
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescence study of defects created by Vickers indentation in hydrothermal ZnO crystals

Abstract: Vickers indentations of ZnO crystals grown by the hydrothermal method were studied by cathodoluminescence. The defects induced by indentation influenced the luminescence spectrum, indicating the generation of non radiative recombination centers and a band close to the first phonon replica of the free exciton, in the surrounding area near the indentation. The possible nature of the defects responsible for such band is discussed. A comparison with polishing induced damage is also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In defect-rich regions the excitonic band is quenched and the defect-related band becomes dominant. The defect-related band is clearly observed in mechanically damaged areas, for example, around the Vickers indentations [18]. In AFRL samples the overall P1 is weak, its intensity being much lower than the BX band; however, it can be more intense than BX in mechanically damaged areas, because of the strong quenching of the BX band and the residual emission due to defects, P D band in this case is dominant.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In defect-rich regions the excitonic band is quenched and the defect-related band becomes dominant. The defect-related band is clearly observed in mechanically damaged areas, for example, around the Vickers indentations [18]. In AFRL samples the overall P1 is weak, its intensity being much lower than the BX band; however, it can be more intense than BX in mechanically damaged areas, because of the strong quenching of the BX band and the residual emission due to defects, P D band in this case is dominant.…”
Section: Resultsmentioning
confidence: 90%
“…In fact, its origin is a matter of controversy; it has been associated with the first LO phonon replica of the free exciton; it is 72 meV away the FXA exciton peak [6]; a donor acceptor pair (DAP) transition [16]; a free to neutral acceptor (e-A1) band [17]; from an exciton bound to extended defects (dislocations) [17]. Recent results around the Vickers indentations have revealed that this band is complex [18], and can consist of two subbands overlapping each other, peaking around 3.31 and 3.29 eV, respectively, which were associated with an exciton bound to a point defect, P D , and the one LO phonon replica of the free exciton, FX-1LO. In general, one observes the convolution of the two bands, which most of the times cannot be separated.…”
Section: Resultsmentioning
confidence: 99%
“…Although this effect is present in both samples, it is more visible in the recrystallized one. On the other hand, the emission of the defects band shows a relative an increase in the region close to the indentation center due to a higher concentration of native defects and dislocations inside the indentation 18 .…”
Section: Resultsmentioning
confidence: 97%
“…20 Both CL and PL research on ZnO demonstrated that mechanical polishing leads to surface and near surface damage, which decreases near band edge (NBE) luminescence efficiency, and forms non-radiative recombination centers (NRRCs) and intrinsic defects such as zinc vacancy (V Zn ) and zinc interstitial (Zn i ). [10][11][12][13][14][15][16][17] PAS studies also show creation of dislocations and vacancy defects in the near and sub-surface region after polishing. 19 Recent DLTS measurements show that mechanical polishing introduced two defect levels at 1.0 and 1.2 eV below the conduction band edge E C whose densities subsequent hydrofluoric acid (HF) etching reduced substantially while restoring bulk carrier densities.…”
mentioning
confidence: 96%
“…Previous research also showed the soft nature of ZnO, [8][9][10] which significantly affects the wafer handling, processing, and manufacture of ZnO-based devices. Polishing induced damage has been investigated by cathodoluminescence (CL), [9][10][11][12][13][14][15] photoluminescence (PL), 16,17 ion channeling, 18 positron annihilation spectroscopy (PAS), 19 and deep level transient spectroscopy (DLTS). 20 Both CL and PL research on ZnO demonstrated that mechanical polishing leads to surface and near surface damage, which decreases near band edge (NBE) luminescence efficiency, and forms non-radiative recombination centers (NRRCs) and intrinsic defects such as zinc vacancy (V Zn ) and zinc interstitial (Zn i ).…”
mentioning
confidence: 99%